Pesquisa de anticorpos anti-PGL-I em pacientes infectados pelo HIV em área endêmica para hanseníase - Madureira, Brunela Pitanga Ramos (2015)
The present study investigated subclinical Mycobacterium leprae infection in human immunodeficiency virus (HIV) infected or uninfected individuals by measuring antibodies against M. leprae phenolic glycolipid I (PGL-I). It also sought to establish whether the serology results correlated with the HIV-infected participants’ state of immunosuppression. This was a cross-sectional study that analysed the anti-PGL-I immunoglobulin M antibody levels in 350 HIV-infected and 350 non-HIV-infected individuals residing in an area endemic for the two investigated conditions. The possible correlation between the state of immunosuppression of the HIV-infected participants (CD4+ cell count, viral load and the use or not of antiretroviral therapy) and anti-PGL-I seropositivity was assessed. Approximately 6% (21/350) of the HIVinfected and 29.1% (102/350) of the non-HIV-infected participants were anti-PGL-I antibody seropositive. The number of anti-PGL-I antibody seropositive individuals was approximately five-fold higher in the non-HIV-infected group, compared with the HIV-infected group. There was no significant correlation between the state of immunosuppression of the HIV-infected participants and the anti-PGL-I serology results. The HIV-infected individuals exhibited less anti-PGL-I antibody production relative to the control group, which may indicate a lower rate of subclinical M. leprae infection and/or lower specific production of this antibody. B cell dysregulation might cause the low anti-PGL-I antibody production in HIV-infected individuals. The patients’ state of immunosuppression did not correlate with the anti-PGL-I serology results.